Geographies of trust: Socio-spatial variegations of trust in insurance. Issue 107 (December 2019) - Tranter, Bruce; Booth, Kate
Abstract: Trust is commonly understood as a mechanism that acts to improve transaction efficiency, or as a structural characteristic of organizations. It is a 'good' thing that can be built and harnessed for economic success. However, this type of conceptualisation maintains trust as a discrete and internally stable entity that is universally applied and cordoned off from socio-spatial complexities. In this paper, we present an empiric on trust in the insurance industry with an eye to reports on declining trust in banks, financial institutions and government. Analysing data from two Australian surveys, we map the social and political correlates of having house and contents insurance, consider how knowledge of insurance related issues and trust in insurance companies is associated with house and contents insurance, and measure how much trust Australians place in insurance companies relative to other public institutions. We use our findings as a spring broad for considering more spatialised understandings of trust and conclude by providing signposts for further geographical trust research - the first, qualitative investigations of the spaces and places of trust and its correlates, and the second, using geodemographics for mapping trust's socio-spatial variegations. In this we contribute to research into the socio-spatial variegations of financial processes and technologies, as well as contributing to work on institutional trust.